Respuesta :

Answer:

2. a. - 1

b.

[tex] - \frac{2}{3} [/tex]

3. a. 4

b. 6

Step-by-step explanation:

[tex]2. \: a. \: \sqrt[3]{ - 1} [/tex]

[tex] = \sqrt[3]{( - 1 )\times ( - 1 )\times( - 1)} [/tex]

= -1 (Ans)

[tex]b. \: \sqrt[3]{ - \frac{8}{27} } [/tex]

Since,

[tex] \sqrt[3]{ - x} = - \sqrt[3]{x} [/tex]

Hence,

[tex] = - \sqrt[3]{ \frac{8}{27} } [/tex]

[tex] = - \sqrt[3]{ \frac{2 \times 2 \times 2}{3 \times 3 \times 3} } [/tex]

[tex] = - \frac{2}{3} (ans)[/tex]

[tex]3. \: a. \: 10 - 2 \sqrt{9} [/tex]

[tex] = 10 - 2 \sqrt{3 \times 3} [/tex]

= 10 - 2 × 3

= 10 - 6

= 4 (Ans)

[tex]b. \: 70 - {( \sqrt[3]{64} )}^{3} [/tex]

[tex] = 70 - \sqrt[3]{ {64}^{3} } [/tex]

[tex] = 70 - \sqrt[3]{64 \times 64 \times 64} [/tex]

= 70 - 64

= 6 (Ans)